Implications of Prevalence and Intensity of Soil-Transmitted Helminthes (STHs) on Rural Farmers’ Productivity in Selected Districts of Sierra Leone - Mohamed Ngegba; Emmanuel Hinckley; Muctar Koroma; Alfred Ngegba; Oladimeji Oladele (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Soil-transmitted Helminths (STH) are among the most prevalent parasitic diseases that impair childhood physical and mental growth, hence hindering economic development. The study was a cross-sectional-designed survey, conducted in three districts in Sierra Leone between December and March 2022 on 625 individual farmers to determine: 1) the prevalence of soil-transmitted helminths; 2) the intensity of soil-transmitted helminths; 3) the effect of the prevalence and intensity on farm productivity, and 4) the implication of these effects on agricultural extension service delivery and the rural livelihood of the selected districts. Stool samples were collected from male and female farmers in fifteen chiefdoms in the selected districts and analyzed using the Kato-Katz technique. A total of 625 individuals were included, among whom 172 (27.0%) were vegetable farmers, 224 (35.8%) were tree-crop farmers and 226 (36.2%) were rice farmers. The result indicates a prevalence of parasitic infection among farmers shown by 58.4% eggs/ova in stool from the three districts. STH prevalence is higher in Bo (64.0%), Koinadugu (56.9%), and Kailahun (51,7%). STH infections, in various ways, affected extension services, delivery and the livelihoods of individual farmers. The recommendation is that farmers and children be periodically dewormed for STH infection in rural areas.